POSTPANDEMIC INNOVATIVE TRENDS IN LOGISTICS, DISTRIBUTION AND SUPPLY CHAIN - Laura Lachvajderová; Kádárová, Jaroslava; Kopec, Ján; Rybárová, Denisa (Advanced Logistic Systems - Theory and Practice, 2022)
This scientific output describes the weaknesses of material flows and the lack of resilience of supply chains, which resulted in the outbreak of the COVID-19 pandemic. This unpleasant situation has presented the whole of logistics with new challenges and problems, which society and industry have tried with their approach to achieving non-stagnant logistics processes, which were therefore threatened mainly by the pandemic. The article describes old but mainly new trends and innovations in logistics, distribution and supply chain, which are also the result of accelerated digital transformation.